AKULTURASI MASYARAKAT LOKAL DAN PENDATANG DI PAPUA BARAT - Raisa Anakotta; Alman Alman; Solehun Solehun (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
The culture was always close to the society and it became their habits in daily life. It would either consciously or unconsciously be derived from their next generations. That was why every community would always have their own culture. West Papua was an example of the Eastern part of Indonesia that was resided by various ethnics groups. In this concern, it would extremely lead to the acculturation of their culture in many aspects. This research aimed to describe the forms of acculturations happened in West Papua between local people and the immigrants and describe how it influenced society. This research was an ethnography research that would be described qualitatively. The study shows that the social diversity in West Papua became a gap for acculturation to their culture. The forms of acculturations were a substitution, syncretism, addition, origination, deculturation, and denial. The cultural acculturations made the society in West Papua could live side by side and they still carried out their respective cultures.